Produksi Biodiesel tanpa Gliserol dari Minyak Kelapa Sawit dengan Variasi Massa Co-solvent dan Waktu Reaksi - Elvianto Dwi Daryono; Puji Prasetyo, Angga; Bahri, Syaiful; Maya Sista, Eliya (Talenta Publisher (Universitas Sumatera Utara), 2020)
Petroleum fuels are increasingly reduced in line with the increasing industry and population. A potential alternative renewable energy source to replace fuel is biodiesel. The process of making biodiesel that is commonly done is the process of transesterification with glycerol byproducts which is difficult to separate. The method used in this study is the method of interesterification, namely by replacing the methyl alcohol group with a methyl group from methyl acetate with triacetin byproducts. The operating conditions of the process are 250 grams of palm oil mass, 1% wt KOH catalyst mass. oil, reaction temperature 60 â°C, stirring speed 800 rpm, mass of co-solvent methyl ester (0, 5, 10, 15, 20% wt. oil) and reaction time (30 minutes, 60 minutes, 90 minutes). The results of the research have been obtained the highest yield with the addition of co-solvent methyl ester of 20% by weight of oil in the reaction time of 30 minutes is 92.43 %.The biodiesel product produced meets SNI 7182:2015 which is an acidic value <0.5 mg-KOH/g.